Bactericidal Property of Oregano Oil Against Multidrug-Resistant Clinical Isolates - Lu, Min; Dai, Tianhong; Murray, Clinton K.; Wu, Mei X. (Frontiers in Microbiology, 2018)
Development of non-antibiotic alternatives to treat infections caused by multidrug-resistant (MDR) microbes represents one of the top priorities in healthcare and community settings, especially in the care of combat trauma-associated wound infections. Here, we investigate efficacy of oregano oil against pathogenic bacteria including MDR isolates from the combat casualties in vitro and in a mouse burn model. Oregano oil showed a significant anti-bacterial activity against 11 MDR clinical isolates including four Acinetobacter baumannii, three Pseudomonas aeruginosa, and four methicillin-resistant Staphylococcus aureus (MRSA) obtained from combat casualties and two luminescent strains of PA01 and MRSA USA300, with a MIC ranging from 0.08 mg/ml to 0.64 mg/ml. Oregano oil also effectively eradicated biofilms formed by each of the 13 pathogens above at similar MICs. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) revealed that oregano oil damaged bacterial cells and altered the morphology of their biofilms. While efficiently inactivating bacteria, there was no evidence of resistance development after up to 20 consecutive passages of representative bacterial strains in the presence of sublethal doses of oregano oil. In vivo study using the third-degree burn wounds infected with PA01 or USA300 demonstrated that oregano oil, topically applied 24 h after bacterial inoculation, sufficiently reduced the bacterial load in the wounds by 3 log10 in 1 h, as measured by drastic reduction of bacterial bioluminescence. This bactericidal activity of oregano oil concurred with no significant side effect on the skin histologically or genotoxicity after three topical applications of oregano oil at 10 mg/ml for three consecutive days. The investigation suggests potentials of oregano oil as an alternative to antibiotics for the treatment of wound-associated infections regardless of antibiotic susceptibility.